Infant locomotive development and its association with adult blood pressure - Pillas, D; Tzoulaki, I; Rodriguez, A; Khan, AA; Elliott, P; Jarvelin, M-R; Kaakinen, M; Netuveli, G; Blane, D; Fung, E; Tammelin, TH; Millwood, IY; et al. (2014)
Evidence from animal models suggests that locomotion and blood pressure share common neurophysiological regulatory systems. As a result of this common regulation, we hypothesized that the development of locomotion in human infants would be associated with blood pressure levels in adulthood. The study sample comprised 4,347 individuals with measures of locomotive and non-locomotive neuromotor development in infancy and adult blood pressure levels within a longitudinal birth cohort study, the Northern Finland Birth Cohort 1966. Later development in all three stages of locomotive development during infancy was associated with higher systolic and diastolic blood pressure levels at age 31. For age of walking without support, 0.34 (95 % CI 0.07 to 0.60)-mm Hg higher SBP and 0.38 (95 % CI 0.15 to 0.62)-mm Hg higher DBP were estimated for each month of later achievement (P = 0.012 for SBP; P = 0.001 for DBP). No association was identified for non-locomotive neuromotor development. Conclusion: These results highlight the positive sequelae of advanced locomotive development during infancy, suggesting that the common regulatory systems between locomotion and blood pressure may influence the development of raised blood pressure over time. © 2014 Springer-Verlag Berlin Heidelberg.